Hermaphrodites and the medical invention of sex - Dreger, Alice Domurat (Harvard University Press, 1998)
"Hermaphrodites and the Medical Invention of Sex takes us inside the doctors' chambers to see how and why medical and scientific men construed sex, gender, and sexuality as they did, and especially how the material conformation of hermaphroditic bodies - when combined with social exigencies - forced peculiar constructions. Throughout the book Dreger indicates how this history can help us to understand present-day conceptualizations of sex, gender, and sexuality. In an epilogue, she discusses and questions the protocols employed today in the treatment of intersexuals (people born hermaphroditic). Given the history recounted, should these protocols be reconsidered and revised?"--Jacket.